The Evolution of Syriac Script and Writing - Dakhel, Huda; Zweir, Mohammed (Al-Adab Journal, 2025)
This research, titled “The Evolution of Syriac Script and Writing”, delves into a significant aspect of the Syriac language—its script and origins. It explores the history of Syriac writing as one of the ancient Semitic languages that played a crucial role in shaping intellectual and cultural development in the Near East, undergoing remarkable transformations throughout history.The study traces the early stages of Syriac writing, analyzing its evolution across different eras. Emerging from the Aramaic alphabet, Syriac script developed through several fundamental phases, influenced by religious, cultural, and political factors that contributed to its spread across diverse communities.Furthermore, this research seeks to deepen our understanding of Syriac script’s impact on literature, religious discourse, and cultural communication. It highlights its vital role in transmitting knowledge and preserving Syriac heritage. By shedding light on the historical significance of Syriac writing, this study contributes to safeguarding the linguistic and cultural identity of Syriac, emphasizing the importance of studying it as an integral part of the region’s cultural and religious legacy.